Food provisioning to Pardosa spiders decreases the levels of tissue-resident endosymbiotic bacteria - Řezáč, Milan; Řezáčová, Veronika; Gloríková, Nela; Némethová, Ema; Heneberg, Petr (Scientific reports, 2023)
The diversity, host specificity, and physiological effects of endosymbiotic bacteria in spiders (Araneae) are poorly characterized. We used 16S rDNA sequencing to evaluate endosymbionts in the cephalothorax and legs of a wolf spider Pardosa agrestis . We tested the effects of feeding once or twice daily with fruit flies, aphids, or starved and compared them to those of syntopically occurring Pardosa palustris . The feeding increased traveled distance up to five times in some of the groups provisioned with food relative to the starved control. The Shannon diversity t -test revealed significant differences between these component communities of the two spider species. The increased frequency of feeding with fruit flies, but not aphids, increased the dominance and decreased the alpha diversity of OTUs. The obligate or facultative endosymbionts were present in all analyzed spider individuals and were represented mostly by Rickettsiella , Rhabdochlamydia , Spiroplasma , and the facultative intracellular parasite Legionella . Vertically transmitted endosymbionts were less common, represented by Wolbachia pipientis and Rickettsia sp. H820. The relative abundance of Mycoplasma spp. was negatively correlated with provisioned or killed aphids. In conclusion, the tissues of Pardosa spiders host tremendously diverse assemblages of bacteria, including obligate or facultative endosymbionts, with yet unknown phenotypic effects.